The Big Nothing or Le Presque Rien - Scharlin, Kerri; French Cultural Services, New York (New York : The New Museum of Contemporary Art, 1992)
Ganahl, Rainer ; Basserode, Jérome ; Antoni, Janine ; Simmons, Gary ; Sander, Karin ; Bogawa, Roddy ; Parsons, Laurie ; Jézéquel, Claire-Jeanne ; Jugnet, Anne-Marie ; etc.
The Big Nothing or Le Presque Rien, The New Museum of Contemporary Art, New York, On view January 15 to April 19, 1992 ; French Cultural Services, New York, On view January 16 to February 28, 1992
boek